Radiocarbon dating of samples of ice wedges near the village of the Baydarata Bay - Vasil'chuk, Yurij K; Budantseva, Nadine A; Tokarev, Igor V; Ginzburg, Alexander P; Vasil'chuk, Alla Constantinovna; Vasil'chuk, Jessica Yurevna (PANGAEA, 2024)
The main purpose of this work is to establish the formation time of Holocene syngenetic ice wedges that have been exposed on the coast of Baydarata Bay near the village of Yarynskaya, 500 m to the southeast from the mouth of the Ngarka-Tambyakha River.Radiocarbon dating of microinclusions of organic matter, extracted directly from three Holocene syngenetic ice wedges, was conducted using accelerator mass spectrometry (AMS). The dating of the wedges correlates to their formation approximately 6.4, 5.0, and 1.9 cal ka BP. A comparison of the oxygen isotopic composition of the Holocene ice wedges (in which the δ18О values vary mainly from -21.8 to -13.73%) and modern ice wedges (the age of which, as a rule, does not exceed 100 years) showed a close range of variations in values. According to isotope oxygen data, the average January air paleotemperature in the Middle and Late Holocene at the coast of the Baydarata Bay was calculated. It is shown that the average January air temperature during this period here varied from about -20 to -25 °C, however, during milder winters it could be about -18 °C. Radiocarbon dating of ice samples and organic microinclusions extracted directly from ice wedges was carried out at the Radiocarbon Laboratory of the Institute of Geography, Russian Academy of Sciences, and the Center for Applied Isotope Research, University of Georgia (United States). The age was calibrated using the IntCal20 curve and Oxcal version 4.4.4 software. The age of organic matter (cal yr BP) from ice wedges was calibrated until 1950.
Keywords: AMS radiocarbon dating; coast of Baydarata Bay; Holocene; Ice wedges; stable oxygen isotopes